Kontribusi Pendidikan Islam dalam Peningkatan Pemahaman Hukum Keluarga Syariah - Atikah Rakhmawati; Dinda Nasya Atin; Tegar Catur Kurniawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic education plays an important role in providing a deeper understanding of sharia family law to the community. This article reviews the concept of sharia family law, including marriage, divorce, and inheritance, and how Islamic education can be an instrument to improve the community's understanding of these issues. This study also identifies challenges in the implementation of sharia family law materials in Islamic educational institutions.